Plant Growth Promoting Activities of Spore-Forming and Vegetative Cells of Salt-Tolerant Rhizobacteria under Salinity Condition: 10.32526/ennrj/20/202100211 - Kidtook, Tiptida; Ekprasert, Jindarat; Riddech, Nuntavun (Environment and Natural Resources Journal, 2022)
Plant growth promoting rhizobacteria are able to enhance plant growth. This study isolated spore-forming rhizobacteria from vegetable rhizosphere soil samples. These isolates were tested for their abilities to promote plant growth and to be used in bio-fertilizers. Thirty-nine isolates with different characteristics were obtained. Three isolates, TYS1.1, TYS3.3, and TYS3.5, showed multifunctional activities on nitrogen fixation and potassium solubilization. They were tested for IAA production in liquid medium supplemented with tryptophan and NaCl, with the vegetative cells of isolate TYS3.5 showing the highest IAA production. The colonization of the three isolates on okra roots was checked by spread plate technique and scanning electron microscope. It was found that rhizobacteria could colonize plant roots with a concentration of 8.19 log CFU/g in the presence of 50 mM NaCl solution. Bio-fertilizer was produced by immobilizing the mixture of three isolates on carriers. The viable cells were enumerated during the storage at room temperature for 60 days. The results showed that the highest number of survival cells in the form of vegetative and spore-forming cells were obtained when using rice husk ash and vermiculite as a carrier. The concentration of viable cells was in a range of 8.14-8.44 log CFU/g. These isolates were Bacillus sp. according to the 16S rDNA sequencing analysis.